Association of NLRP3 rs35829419 and rs10754558 Polymorphisms With Risks of Autoimmune Diseases: A Systematic Review and Meta-Analysis - Wu, Zubo; Wu, Suyuan; Liang, Tao (Frontiers in Genetics, 2021)
The existing knowledge about the association between NLRP3 rs35829419/rs10754558 polymorphisms and susceptibility to autoimmune diseases (AIDs) remains controversial. Herein, a meta-analysis was performed to evaluate such association. We searched databases for relevant studies published in English up to February 2021. Stata12 was used to assess the odds ratio (OR). As for NLRP3 rs35829419, no significant association to overall AIDs was found in three genetic models [A vs. C: OR (95%CI) =0.89 (0.69-1.14); AC vs. CC: 1.00 (0.77-1.30); AA/AC vs. CC: 0.93 (0.71-1.20)]. However, subgroup analysis by disease type showed that NLRP3 rs35829419 A allele may have a significant protective effect on rheumatoid arthritis (RA) susceptibility [A vs. C: 0.74 (0.57-0.96)]. NLRP3 rs10754558 polymorphism contributes to significantly reduce the risk of AIDs in the allelic model [G vs. C: 0.78(0.71-0.87)], homozygote co-dominant model [GG vs. CC: 0.63(0.51-0.77)], heterozygote co-dominant model [GC vs. CC: 0.78(0.66-0.91)], dominant model [GG/GC vs. CC: 0.73(0.63-0.84)] and recessive model [GG vs. GC/CC: 0.73(0.62-0.88)]. In the subgroup analysis by ethnicity, association was observed between the NLRP3 rs10754558 G allele and AIDs in Latin Americans, but not in European, Arabian or Asian populations. Stratification by disease type showed a significant association of the NLRP3 rs10754558 G allele with type 1 diabetes, RA and systemic lupus erythematosus, but not with celiac disease, multiple sclerosis or myasthenia gravis. This meta-analysis suggests that the NLRP3 rs10754558 but not rs35829419 polymorphism is associated with susceptibility to AIDs, especially in Latin American individuals.